Histological study of different oviduct parts of Gallus domesticus - Ayad Hameed Ebrahim; Shurooq Hameed Majeed; Israa Hashim Ali (Tikrit Journal of Pure Science, 2023)
This study included the histological structure of the oviduct of white chicken, The wall of this duct consisted of four layers, the mucosa made up from pseudostratified columnar epithelium, the epithelium is continuous layer of columnar cells with alternating basal cells which stand on the loose connective tissue form the lamina propria, the mucosa forms leaf shaped longitudinal folds contained glands which lined with cuboidal cells , the second layer was the submucosa which was loose connective tissue, The muscularis was the third layer contained smooth muscle with an inner circular and outer longitudinal layers. loose connective tissue formed the serosa